Soil Characteristics Involved in Phosphorus Sorption in Mollisols. Issue 6 (8th December 2016) - Cabello, Maria Julia; Gutiérrez Boem, Flavio H.; Quintero, Cesar E.; Rubio, Gerardo
Abstract : Core Ideas: Predictive models of phosphorus sorption were developed for a group of Mollisols. Alox was the best predictor of short‐term phosphorus sorption indices. Feox was the best predictor for those indices that involves longer interaction periods. Phosphorus needs to maximize yield avoiding environmental risks can be estimated with our data. The role of different soil properties on defining the P sorption capacity was investigated in a group of Mollisols of the Pampean Region (Argentina). Two‐single point and three‐multiple point P sorption indices were evaluated. Both simple and multiple regression models indicated that ammonium oxalate extractable Al (Alox ) and ammonium oxalate extractable Fe (Feox ) were the main properties defining P sorption. Ammonium oxalate extractable Al prevailed as the best predictor of short‐term P sorption indices and Feox as the best predictor for those indices that involves longer interaction periods. After Alox and Feox, the best correlations were obtained for the sum of Ca and Mg. The higher P retention of soils located in the Southern part of the Region was associated with the parental material rather than with anthropogenic effects. Obtained information can strengthen P fertilization programs by providing a methodology to estimate fertilizer P requirements to optimize crop yields while reducing environmental risks.